REGIONAL DEVELOPMENT EFFORTS THROUGH ECONOMIC EMPOWERMENT OF THE JABUNG DISTRICT COMMUNITY - Hermanda, Agus Iprah; Hafifah, Wardatul; Murotul, Fatma Kana (Universitas Islam Malang, 2024)
This research entitled